Metal sewing-thimbles found in Britain - Read, Brian, 1939- (Archaeopress Publishing Ltd, 2018)
This reference work deals specifically with all types of sewing-thimble made from copper-alloy or silver, or either of these materials combined with iron or steel, and found in Britain. Domed, ring-type and open-top sewing-thimbles are described, among them unusual examples and others previously absent from the known record.